The Automatic Activation of Sound-Letter Knowledge: An Alternative Interpretation of Analogy and Priming Effects in Early Spelling Development - Nation, K; Hulme, C (1996)
This paper presents two experiments investigating 6-year-old children's use of analogy in spelling. In Experiment 1, children make analogies between a visible clue word and a similar sounding target word. Analogies are made to the same extent regardless of whether the clue and target share a rime unit, a consonant vowel (CV) or a vowel but are not made when only common letters are shared. A second experiment investigates children's spelling by analogy when the clue word is not visible. Again, an equal number of analogies are made between words sharing a rime unit, a CV or a vowel. From the earliest stages of learning to spell, children benefit from drawing analogies (at the level of individual phonemes) with words that they know. These findings are related to recent connectionist models of the development of reading and spelling skills.